Satire of the World War II Reflected in AD Poem by Kenneth Flexner Fearing - Kusdiati, Kusdiati (LANTERN (Journal on English Language, Culture and Literature), 2017)
In this thesis, the writer analyzes a poem entitled Ad by Kenneth Flexner Fearing. The poem tells about World War II that contents satire. The writer uses satire as a theme because satire is element of art that uses to criticize or to show a stupidity or corruption of an individual or group toward other people that is illustrated with humor, mock and exaggerated statement and a ridiculous thing that make the other people laugh. The writer uses the satire in this poem because it can change or improve people’s behavior into better quality. The writer analyzes satire in intrinsic element of Ad such as satire in the diction, symbol and imagery. The writer also analyzes satire in the extrinsic element and condition of society in the poem through the sociology approach. For the method of analysis, the writer uses library research which is the writer takes many resources from library such as journals, book etc that can be used as the main information. The writer also uses internet resources to provide more information that is needed. The result of the thesis shows that the poem satirizes the society that lives in the World War II era.